Framework Of Strategic Alignment Through Enterprise Architecture For Organization Performance - Yoppy Mirza, Maulana; Zafril Rizal, M Azmi; Ruzaini, Abdullah Arshah; Muhammad Aliif, Ahmad; Halah, Zain (Institute of Electrical and Electronics Engineers Inc., 2021)
One of the topics in strategic planning of information systems is Business-IT alignment (BITA). BITA is manifested in strategic alignment, which is generally seen as an important factor as a driver for optimizing business performance. Strategy conformity is related to the suitability of internal resource capabilities and external opportunities towards superior performance. To realize the suitability of Business and IT strategies, a framework is needed, namely Enterprise Architecture (EA). Many studies have focused on business and IT customization using EA, but none have addressed how to relate it to organizational performance. Meanwhile, the goal of IT investment is to improve organizational performance by aligning IT with the business. For this reason, the solution is to develop a framework for conformity with Business and IT strategies through EA by mapping organizational performance. The resulting output is a framework used to align IT with business strategy through EA and its relationship to organizational performance.